The hidden causes of pregnancy loss: a closer look - Panlai Shi; Conghui Wang; Hongbin Liang; XiaoFan Zhu; Xinyan Wang; Yanting Ning; Don Leigh; David S. Cram; Xiangdong Kong (Journal of Translational Medicine)
Abstract Background Unexpected pregnancy loss can be a traumatic experience for fertile couples. The aim of the study was to assess the nature and type of chromosomal variants involved in early and late pregnancy loss and provide couples an explanation on the cause of their pregnancy loss. Methods Investigations were conducted on 2928 pregnancy loss cases where products of conception (POC) samples could be retrieved for genetic analysis. Chromosomal variants were detected by low pass copy number variation sequencing (CNV-seq). Results In first-trimester miscarriages, 1272 of POC (60.4%) samples had a chromosome abnormality. Autosomal aneuploidy and monosomy X were the predominate variants (73.2%), followed by autosomal and sex chromosome mosaicism (10.7%), triploidy (9.6%), pathogenic CNVs (6.2%) and haploidy (0.3%). The chromosomal variants were similar in type and frequency regardless of whether the fetus had normal or abnormal ultrasound findings. In second trimester pregnancy loss where there was either a structural or non-structural ultrasound anomaly, only 15.3% of POC samples had a chromosome abnormality, involving mainly the smaller autosomes and monosomy X (55.7%), autosomal and sex chromosomal mosaicism (11.5%), triploidy (4.1%) and pathogenic CNVs (28.7%). Conclusion Chromosomal variants contribute to fetal demise in almost two thirds of pregnancy losses.